Programmable C‐to‐U RNA editing using the human APOBEC3A deaminase. (3rd May 2021) - Huang, Xinxin; Lv, Junjun; Li, Yongqin; Mao, Shaoshuai; Li, Zhifang; Jing, Zhenyu; Sun, Yidi; Zhang, Xiaoming; Shen, Shengxi; Wang, Xinxin; Di, Minghui; Ge, Jianyang; et al.
Abstract :